Farm animals can help millions of women raise the well-being of their households - International Livestock Research Institute (International Livestock Research Institute, 2010)
ILRI scientist Jemimah Njuki argues for using animal agriculture to help redress skewed resources available to rural women worldwide. In societies where women are unable to own anything else, farm animals provide women with incomes. And when those women's incomes rise, the health, nutrition and education of their whole families also rise, with everybody winning.